PENGEMBANGAN MEDIA PEMBELAJARAN PAI BERBASIS KUIS INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Koharuddin; Imam Syafe'i; Nanang Supriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and evaluate the effectiveness of Islamic Religious Education (PAI) learning media based on interactive quizzes using Canva to improve student learning outcomes at the junior high school (SMP) level in Padang Cermin District, Pesawaran Regency. The background of this research lies in the low student engagement and lack of internalization of religious values due to the dominance of theoretical approaches, limited interaction, and minimal use of technology in PAI instruction. The research employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The development process involved needs analysis, media design, product creation, limited trials, and effectiveness evaluation. Expert validation indicated the media was highly valid and practical. Paired sample t-test results showed a significance value of 0.001 < 0.05, indicating a significant improvement in student learning outcomes. The N-Gain score of 0.6351 fell into the medium category.